Cardiac responses to 24 hrs hyperoxia in Bmp2 and Bmp4 heterozygous mice. (22nd July 2013) - Howden, R.; Cooley, I.; Van Dodewaard, C.; Arthur, S.; Cividanes, S.; Leamy, L.; McCann Hartzell, K.; Gladwell, W.; Martin, J.; Scott, G.; Ray, M.; Mishina, Y.
Abstract: Background : Hyperoxia or clinical oxygen (O2 ) therapy is known to result in increased oxidative burden. Therefore, understanding susceptibility to hyperoxia exposure is clinically important. Bone morphogenetic proteins (BMPs) 2 and 4 are involved in cardiac development and may influence responses to hyperoxia. Methods. Bmp2 +/ − . Bmp4 +/ − and wild-type mice were exposed to hyperoxia (100% O2 ) for 24 hrs. Electrocardiograms (ECG) were recorded before and during exposure by radio-telemetry. Results : At baseline, a significantly higher low frequency (LF) and total power (TP) heart rate variability (HRV) were found in Bmp2 +/ − mice only ( p  < 0.05). Twenty-four hours hyperoxia-induced strain-independent reductions in heart rate, QTcB and ST-interval and increases in QRS, LF HRV and standard deviation of RR-intervals were observed. In Bmp4 +/ − mice only, increased PR-interval (PR-I) (24 hrs), P-wave duration (P-d; 18 and 21–24 hrs), PR-I minus P-d (PR – Pd; 24 hrs) and root of the mean squared differences of successive RR-intervals (24 hrs) were found during hyperoxia ( p  < 0.05). Discussion : Elevated baseline LF and TP HRV in Bmp2 +/ − mice suggests an altered autonomic nervous system regulation of cardiac function in these mice. However, this was not related to strain specific differences in responses to 24 hrs hyperoxia. During hyperoxia, Bmp4 +/− mice were the most susceptible in terms of atrioventricular conduction changes and risk of atrial fibrillation, which may have important implications for patients treated with O2 who also harbor Bmp4 mutations. This study demonstrates significant ECG and HRV responses to 24 hrs hyperoxia in mice, which highlights the need to further work on the genetic mechanisms associated with cardiac susceptibility to hyperoxia.